All Days 1995
DOI: 10.2118/29134-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Hydraulics Model for Horizontal Wells

Abstract: SPE Members Abstract A horizontal well usually yields a high rate through its long perforation interval, resulting in a large frictional pressure drop that is believed to reduce the well productivity. Unlike conventional horizontal well methods which consider the horizontal section only, the proposed model also includes the vertical section of the well and the surface facility from the well head to the GOSP. The hydraulics model was validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Studies have shown that Dikken (1990) is unrealistic based on assumption of infinite flow conductivity in the horizontal section of the well that was applied in his model derivation. Though several accessible mathematical models (Landman, 1994;Ozkan et al, 1993;Penmatcha et al, 1997;Siu and Subramanian, 1995;Yildiz and Ozkan, 1998) that considered finite flow conductivity in derivation for predicting the productivity of horizontal wells have been coded and generated into commercial software in the oil industry, but rarely attractive due to the common nature of either simplicity if it too analytical or rigorous and time consuming in computation if it too numerical. The mathematical models used for predicting horizontal drain hole productivity that are available fall into three categories: (1) simple analytical solutions derived in late 1980s and early 1990s based on the assumption of frictionless drain holes, Generally, these models are embraced because they are simple and very easy to use.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Dikken (1990) is unrealistic based on assumption of infinite flow conductivity in the horizontal section of the well that was applied in his model derivation. Though several accessible mathematical models (Landman, 1994;Ozkan et al, 1993;Penmatcha et al, 1997;Siu and Subramanian, 1995;Yildiz and Ozkan, 1998) that considered finite flow conductivity in derivation for predicting the productivity of horizontal wells have been coded and generated into commercial software in the oil industry, but rarely attractive due to the common nature of either simplicity if it too analytical or rigorous and time consuming in computation if it too numerical. The mathematical models used for predicting horizontal drain hole productivity that are available fall into three categories: (1) simple analytical solutions derived in late 1980s and early 1990s based on the assumption of frictionless drain holes, Generally, these models are embraced because they are simple and very easy to use.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to theoretical models, some researchers have simulated wellbore flow using numerical techniques to avoid simplifying assumptions (Ouyang and Huang, 2005;Yuan et al 1998;Su and Lee, 1995;Siu et al 1995;Seines et al 1993;Folefac et al 1991). Guo et al (2006) developed a numerical model to study the deliverability of multilateral wells.…”
Section: Reservoir and Wellbore Flow Modelsmentioning
confidence: 99%